Investıgatıon Of Relatıonshıps Be-Tweens Hyoid Bone Posıtıon And Pharyngeal Aırway Adequacy, Tongue And Mandıble Posture In Subject Wıth Dıfferent Cervıcal Postures - Dilek Erdem; Hatice Gökalp; Handan Çamdeviren (Galenos Yayinevi, 1998)
Lateral cephalograms taken at natural head posture of 52 subjects (21 males,, 31 females) in the age range of 19-29 years were used to examine the relations between hyoid bone position and naso-oropharyngeal airway adequacy, tongue posture and mandible posture in three groups comprising subjects with average, forward, and vertical cervical posture. Groups were formed by using the postural angle CVT-HOR. Results revealed that hyoid bone position exhibited statistically significant correlations with naso-oropharyngeal airway adequacy, tongue and mandible posture in groups comprising subjects with forward and vertical cervical postures, whereas in the average cervical posture group, the associations were found to be very few and low.